Kualitas Pelayanan Kantor Otoritas Pelabuhan Utama Tanjung Priok Terhadap Kepuasan Masyarakat Pada Triwulan II Tahun 2023 - Arraini, Vionita; Batu, Reminta Lumban (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research was conducted to find out and describe the service quality of the Tanjung Priok Main Port Authority Office using a descriptive research type through a quantitative approach with reference to Law Number 25 of 2009 and Regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 14 of 2017 which has been adjusted to Service Standards in accordance with PM Transportation Number 19 of 2017. The sample technique used in this study was incidental sampling and the data collection instruments used were questionnaires, observations and interviews. The data collection instruments in this study were questionnaires, observations and interviews with 8 (eight) indicators including information, requirements, procedures/flow, completion time, rates/fees, facilities and infrastructure, responses and consultations and complaints. Based on the results of the research conducted, the service quality provided by the Tanjung Priok Port Authority Office is very good.